Multi-physics modeling of thermochemical heat storage with enhance heat transfer. (5th November 2021) - Shi, Tao; Xu, Huijin; Qi, Cong; Lei, Biao; Wu, Yuting; Zhao, Changying
Highlights: A multi-physical model of CaO/Ca(OH)2 hydration process is simulated. Thermal conductivity of solid-phase has a significant effect on hydration process. Relationships between fins and reaction are explored. Axial fins shorten the exothermic time to 83.4%. Abstract: Thermochemical heat storage technology is an important component in energy system, and plays a key role in the balance of energy supply and demand. A multi-physics model is constructed to study the hydration process in a tubular reactor, including fluid flow, heat transfer and reaction. Variations of temperature and conversion of CaO are discussed in detailed to reveal exothermic reaction characteristics. Besides, effects of different reaction conditions during hydration are studied, such as porosity, temperature, pressure, flow rate and thermal conductivity. It is found that the low thermal conductivity of solid-phase is the most important factor which limits the reaction. The heat transfer process can be greatly promoted by adding fins, due to the high heat conductivity. However, the relationship between the reactor structure and the performance of the thermochemical heat storage is not quantitatively clear. The present study aims to investigate the impact of the arrangement of fins on the hydration process. Finally, different types of fins with high thermal conductivity are employed in the reactor. Attributing to the fact that the equilibrium temperature is affected by the vapor pressure, thermochemical reactors with different fin configurations have different flow characteristics and pressure drops, leading to different reaction characteristics. It is shown that the exothermic time was reduced to 84.32% (axial fins), 89.97% (radial fins), and 88.71% (spiral fins) of the original, respectively. This study can reveal the coupling relations of multi-physics fields in thermochemical heat storage, and provide theoretical basis for the design of thermochemical heat storage reactors.